2004
DOI: 10.1038/sj.hdy.6800554
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of within population dispersal and mating of the fungus Microbotryum violaceum parasitising the plant Silene latifolia

Abstract: This study explores the patterns of dispersal and mating of the anther smut Microbotryum violaceum, a model species in genetics and evolutionary biology. A French metapopulation of the fungus collected from its caryophyllaceous host Silene latifolia was analysed using microsatellites. The genetic diversity was low, populations were strongly differentiated, and there was no pattern of isolation by distance among populations. There was a strong deficit in heterozygotes, confirming the high self-fertilisation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 45 publications
(80 reference statements)
8
80
0
Order By: Relevance
“…In accordance with published microsatellite-based results (Bucheli et al, 2001;Giraud, 2004; Granberg et al, 2008), we observed a very low proportion of heterozygotes in our sequence data in M. violaceum: only two out of the nineteen individuals in our study had any heterozygous sites in any of the non-mating-type-linked loci studied. A high degree of selfing inflates homozygosity, which leads to a low effective recombination rate in the recombining regions and reduces the difference between the recombining and non-recombining regions.…”
Section: Dna Polymorphism and Selfingsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with published microsatellite-based results (Bucheli et al, 2001;Giraud, 2004; Granberg et al, 2008), we observed a very low proportion of heterozygotes in our sequence data in M. violaceum: only two out of the nineteen individuals in our study had any heterozygous sites in any of the non-mating-type-linked loci studied. A high degree of selfing inflates homozygosity, which leads to a low effective recombination rate in the recombining regions and reduces the difference between the recombining and non-recombining regions.…”
Section: Dna Polymorphism and Selfingsupporting
confidence: 93%
“…This leads to high degree of selfing, which is expected to reduce diversity throughout the genome. Indeed, the analysis of microsatellite diversity revealed high homozygosity (Bucheli et al, 2001;Giraud, 2004;Granberg et al, 2008). However, DNA diversity in M. violaceum populations has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses using microsatellites have shown strong heterozygote deficiencies in M. violaceum populations infecting the host S. latifolia (25,39). Further, studies on the meiotic segregation of amplified fragment length polymorphism variation revealed heterozygosity in the genome to be largely restricted to the regions linked to mating type and absent from the autosomes (56).…”
Section: Heterothallism Versus Outcrossing Selfing and Intratetrad mentioning
confidence: 99%
“…Metapopulations of M. violaceum have been shown to follow an island model dynamics where no isolation by distance can be detected among populations (Delmotte et al, 1999;Giraud, 2004). In our model, a fraction m P ¼ 0.125 of the diseased plants in a given patch send teliospores towards any of the other occupied patches, After among-patch dispersal, probability of extinction is calculated for each occupied patch depending on the total number of plants in a patch (N t ), and the extinction coefficient K ext ¼ 0.9.…”
Section: Among-patch Dynamics (Figure 1)mentioning
confidence: 99%
“…This is likely to be rare as pollinators exhibit a strong preference for healthy plants (Jennersten, 1988;Shykoff and Bucheli, 1995). Furthermore, within-population distributions of M. violaceum spores (Roche et al, 1995) and genotypes (Giraud, 2004) reflect strongly the leptokurtic dispersion, suggesting that mixtures of strains may rarely be deposited on healthy plants. The results of model B imply that it would not be useful to search for an advantage of biased strains in competition situations anyway, and that such advantage, as the slight withinhost competitive advantage of strains with a biased sexratio reported by Hood (2003), would be irrelevant to understand haplo-lethal maintenance.…”
Section: Genetic Polymorphism and Antagonistic Pleiotropymentioning
confidence: 99%